The Accountant, Data Collection and Social Exchange . - McDonough, John J. (The Accounting Review, 1971)
This article examines the management of data collection and social exchange by accountants. Perhaps the most provocative element of this article concerns the degree to which the social exchange framework challenges the potency of the authority vested in the controllership role insofar as eliciting cooperation with requests for information. The skepticism with which this argument is typically received tells us a great deal about the expectations which attend data gathering efforts. What is significant about this set of attitudes is that our framework tells us that nothing is likely to have a more disrupting effect on an exchange than a mismatch in views as to the rights and obligations of each party to the exchange by way of the other. The very expectation on the part of financial managers as to the primacy of their activities and position is likely to impede their data gathering efforts. The misconception that appears to exist concerning the ability of the informant to avoid cooperation stems largely from another misconception–that managers are capable of framing sharp questions which cannot be avoided short of open defiance. In truth, the bulk of management's information requirements merely serve to provide sufficient background to permit the posing of the more penetrating substantive questions. It is the instrumental nature of management inquiry which provides the operating level with an ability to limit its cooperation.